2016
DOI: 10.17795/ijpbs-3993
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Evaluation in Iranian Postpartum Women With and Without Striae Gravidarum

Abstract: BackgroundStriae are a common change during pregnancy, leaving striae in various body parts after delivery, which most women find unpleasant. They create a big aesthetic concern for most women. Although striae do not endanger the mother and the fetus, they may cause a desire to scratch the region leading to small wounds, induce stress over beauty, decrease self-confidence, and create psychological disorders. They may try various treatments and often refer to dermatology clinics and receive long-term treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Вместе с тем те немногие результаты исследований качества жизни пациенток со striae gravidarum свидетельствуют о некотором ухудшении данного показателя [12,13].…”
Section: качество жизниunclassified
“…Вместе с тем те немногие результаты исследований качества жизни пациенток со striae gravidarum свидетельствуют о некотором ухудшении данного показателя [12,13].…”
Section: качество жизниunclassified
“…However, some studies reported that Iranian skin types, based on Fitzpatrick scale, can be classified as "lightly pigmented", i.e. skin types I to IV from north to south, respectively, based on the Fitzpatrick scale (57)(58) and there is no relationship between skin type and minimal erythermal dose (59). We did not examine any possible association between NMSC and other VDR polymorphisms, including BsmI.…”
Section: Several Studies Have Examined the Possible Interactions Betwmentioning
confidence: 99%
“…Researchers are generally restricted to evaluating isolated characteristics, such as the length and width of the striae, assessing ultrasonography parameters or considering subjective criteria, such as the patient's or physician's satisfaction. [11][12][13][14][15][16][17][18] The optimal outcome of SD treatment is its total clearance. 19 As this result is not attainable in most patients with current treatments, objective measures to classify SD and compare the efficacy of therapies are valuable in clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…There is still no objective instrument that considers all relevant, sensitive, and accurate clinical aspects for the assessment of stretch marks before and after controlled treatment to measure the degree of improvement. Researchers are generally restricted to evaluating isolated characteristics, such as the length and width of the striae , assessing ultrasonography parameters or considering subjective criteria, such as the patient's or physician's satisfaction 11‐18 …”
Section: Introductionmentioning
confidence: 99%